Conformal Killing Vector Fields of Riemannian Manifolds (Dhaka University Journal of Science, 2022)
The main aim of this article to study about vector fields of manifold and how these vector fields will be Killing and Conformal Killing vector fields. Conformal transformation of Weyl rescaling which is conformally related to metrices from g to g, Levi-Civita connection Δ , Lie derivative, torsion with tensor concept of manifold N in a multi-linear map have been treated in this paper. Finally, we have been proved Example 3.02and established the theorem 6.02 on Conformal Killing vector fields.Dhaka Univ. J. Sci. 70(2): 18-22, 2022 (July)